Comparative-effectiveness research of COVID-19 treatment: a rapid scoping review. Issue 6 (3rd June 2022) - Pham, Ba; Rios, Patricia; Radhakrishnan, Amruta; Darvesh, Nazia; Antony, Jesmin; Williams, Chantal; Ramkissoon, Naveeta; Cormack, Gordon V; Grossman, Maura R; Kampman, Melissa; Patel, Milan; Yazdi, Fatemeh; et al.
Abstract : Objectives: The COVID-19 pandemic has stimulated growing research on treatment options. We aim to provide an overview of the characteristics of studies evaluating COVID-19 treatment. Design: Rapid scoping review Data sources: Medline, Embase and biorxiv/medrxiv from inception to 15 May 2021. Setting: Hospital and community care. Participants: COVID-19 patients of all ages. Interventions: COVID-19 treatment. Results: The literature search identified 616 relevant primary studies of which 188 were randomised controlled trials and 299 relevant evidence syntheses. The studies and evidence syntheses were conducted in 51 and 39 countries, respectively. Most studies enrolled patients admitted to acute care hospitals (84%), included on average 169 participants, with an average age of 60 years, study duration of 28 days, number of effect outcomes of four and number of harm outcomes of one. The most common primary outcome was death (32%). The included studies evaluated 214 treatment options. The most common treatments were tocilizumab (11%), hydroxychloroquine (9%) and convalescent plasma (7%). The most common therapeutic categories were non-steroidal immunosuppressants (18%), steroids (15%) and antivirals (14%). The most common therapeutic categories involving multiple drugs were antimalarials/antibiotics (16%), steroids/non-steroidal immunosuppressants (9%) and antimalarials/antivirals/antivirals (7%). The most common treatments evaluated in systematic reviews were hydroxychloroquine (11%), remdesivir (8%), tocilizumab (7%) and steroids (7%). The evaluated treatment was in favour 50% and 36% of the evaluations, according to the conclusion of the authors of primary studies and evidence syntheses, respectively. Conclusions: This rapid scoping review characterised a growing body of comparative-effectiveness primary studies and evidence syntheses. The results suggest future studies should focus on children, elderly ≥65 years of age, patients with mild symptoms, outpatient treatment, multimechanism therapies, harms and active comparators. The results also suggest that future living evidence synthesis and network meta-analysis would provide additional information for decision-makers on managing COVID-19.